2012
DOI: 10.1149/1.3694338
|View full text |Cite
|
Sign up to set email alerts
|

Dry Etching Solutions to Contact Hole Profile Optimization for Advanced Logic Technologies

Abstract: As CMOS technology has been continuously scaling down and the dual-stress liner scheme is introduced for simultaneous stress enhancement of both n-MOS and p-MOS, contact etch has started to act as a critical role for the robust performance of integrated circuit. In this work, we investigated the impact of dry etching process on contact hole profile. Results demonstrate the overall contact hole profile can be rigorously controlled if the radio frequency (rf) powers and etching chemistries in inter layer dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Lower CxFy/O2 ratio could lead to bigger AEI CD, lower contact open risk and lower Oxide-to-CESL selectivity. Condition 3 is the current-best performance [3] .…”
Section: Schemes Of CD Shrinkage In Contact Etch Processmentioning
confidence: 99%
“…Lower CxFy/O2 ratio could lead to bigger AEI CD, lower contact open risk and lower Oxide-to-CESL selectivity. Condition 3 is the current-best performance [3] .…”
Section: Schemes Of CD Shrinkage In Contact Etch Processmentioning
confidence: 99%
“…Previous studies already showed the contact profile of CESL part also needs to be well controlled to ensure the good profile to avoid the potential contact to gate bridge and less silicide loss performance for the concern of leakage. [6] Silicon loss at the bottom of share contact hole was highlighted as another key issue of junction leakage as shown in Figure 6. This is caused by excessive over-etch percentage of CESL together with the insufficient height and profile of spacer wall.…”
Section: Effect Of Etch Chemistry In Lrm Process On Silicon Loss and ...mentioning
confidence: 99%